The Challenges of Developing an Indonesian Travel Corridor: Bintan Resorts in Singapore as a Study Case - Fera, Mirta; Muzwardi*, Ady; Oktavian, Dimas (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2024)
Indonesia has the best international cross-border tourism called Bintan Resorts or better known as Lagoi. The emergence of Covid-19 made the tourism sector in Lagoi slumped. This condition makes Bintan Resorts and tenants, local governments, and the central government strive to revive Lagoi tourism through promotion by using a business diplomacy strategy through a travel bubble approach to attract Singaporean tourists as Lagoi's main target market. This research uses a qualitative method that shows the results that the concept of a travel bubble between Bintan Resorts and Singapore has not been fully implemented. This is because Indonesia's diplomacy has not been followed by domestic policies that are consistent and of the same standard as Singapore. This study argues the need for a middle ground in the form of a mutual agreement, where the Indonesian government can apply all Singaporean requirements as national standards, especially in tourism management. Keywords: Economy; Management; Travel Bubble; Business; Building Capacity